Improving Students' Vocabulary Mastery Through Digital Mind Mapping for Twelfth-Grade Students of SMA Negeri 1 Tanjung Palas - Mariana Mariana; Ari Purnawan (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This classroom action research investigated the use of digital mind mapping through the Miro platform to enhance vocabulary mastery and classroom participation among twelfth-grade students at SMA Negeri 1 Tanjung Palas. The study was motivated by preliminary evidence showing students’ reliance on direct translation, difficulty in retaining words, and hesitation in contextual usage. Conducted in two cycles of planning, action, observation, and reflection, the research involved 31 students of Class XII B. Data were collected through vocabulary tests, classroom observations, and semi-structured interviews, then analyzed both quantitatively and qualitatively. Results indicated gradual improvement in vocabulary mastery and learning processes. The class mean score increased from 42.26 in the pre-test to 68.63 after Cycle 1 and 77.66 after Cycle 2, with 77.42% of students achieving the Learning Objective Achievement Criteria (KKTP) of 75.00. The mean N-Gain of 0.61 reflected moderate improvement. Observational data revealed a shift from passive translation-based learning to active vocabulary organization using branches, colors, images, and contextual examples. Technical challenges in Cycle 1 were mitigated in Cycle 2 through structured templates and teacher scaffolding, resulting in more confident collaboration and contextualized sentence production. These findings suggest that digital mind mapping, when supported by equitable access and teacher guidance, can effectively improve vocabulary learning and reduce classroom anxiety.